Psychometric Properties and Factor Structure of the University Readiness Survey - Al-Kalbani, Muna; Al Barwani, Thuwayba; Neisler, Otherine; Alkharusi, Hussain; Clayton, David; Al-Sulaimani, Humaira; Khan, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This study describes the psychometric properties and factor structure of the University Readiness Survey (URS). Survey data were collected from a sample of 2652 students from Sultan Qaboos University. Exploratory factor analysis identified ten significant factors underlining the structure. The results of Confirmatory factor analysis showed a good fit to the data where the indices for the revised model were χ2 (df = 1669) = 6093.4; CFI = 0.900; GFI =0.926; PCLOSE = 1.00 and RMSAE = 0.030 where each of these indices were above threshold. The overall value of Cronbach’s alpha was 0.899 indicating that the instrument score was reliable. Results imply that the URS is a valid measure describing the college readiness pattern among Sultan Qaboos University students and the Arabic version could be used by university counsellors to identify students’ readiness factors. Nevertheless, further validation of the USR is recommended.